Fluoride in tea from Shandong Province, China and exposure assessment. Issue 2 (2nd April 2020) - Shao, Lijun; Xu, Shiming; Wang, Guoling; Yang, Luping; Li, Renpeng; Zhu, Jing; Chen, Jindong; Jiang, Dafeng
ABSTRACT: In this study fluoride in 170 tea samples from Shandong province (China) was determined using a selective ion electrode. The fluoride concentrations ranged from 31.2 to 338 mg/kg with an average of 119 mg/kg. The mean fluoride concentrations were 164, 121, 98.7 and 96.8 mg/kg, which corresponded to Pu'erh tea, green tea, oolong tea and black tea, respectively. Moreover, 4.7% of the analysed samples exceed the legal limit of 200 mg/kg recommended by China. The estimated daily intake of fluoride via drinking tea for an adult was between 0.655 and 1.07 mg/person/day, which were lower than the provisional maximum tolerable daily intake value of 3.5 mg/person/day set by the National Health and Family Planning Commission of the People's Republic of China. In future, maintaining a surveillance programme to monitor the trend of fluoride in tea is necessary for food safety and human health.